2019
DOI: 10.1016/j.heliyon.2019.e02956
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antimicrobial resistance patterns of burn wound infections in a tertiary care hospital

Abstract: BackgroundThe bacterial infections that prevail in the burnt patients continue to be a critical complication in the burnt patients and vary with time and place. Identification of bacterial pathogens with information of their antimicrobial susceptibility of burn wounds can help clinicians to select appropriate medication procedure as in providing them with suitable antibiotic for empirical treatment.MethodsRetrospective study of thirty-one months (Jan 2015 to July 2017) was designed to evaluate bacteria involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 20 publications
7
27
3
1
Order By: Relevance
“…Among the isolates, P. aeruginosa was found to be predominate which accounted for 13.99% of total isolates. This result is in concordance with previous reports (Agnihotri et al 2004;Gupta et al 2019), where the same bacteria is most frequently isolated but is in contrast to other studies which report S. aureus as predominant organism (Lesseva and Hadjiiski 1996;Komolafe et al 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the isolates, P. aeruginosa was found to be predominate which accounted for 13.99% of total isolates. This result is in concordance with previous reports (Agnihotri et al 2004;Gupta et al 2019), where the same bacteria is most frequently isolated but is in contrast to other studies which report S. aureus as predominant organism (Lesseva and Hadjiiski 1996;Komolafe et al 2003).…”
Section: Discussionsupporting
confidence: 93%
“…These organisms may further cause disseminated infection following colonization and it has been estimated that 75% of all deaths in burnt patients were associated with infections. As the etiology of burn wound changes with time, the expanded use of antibiotics leads to the development as well as selection of multidrug resistant (MDR) bacteria which results in treatment failure and intensifi es the complications (Srinivasan et al 2009;Gupta et al 2019). The Gram negative pathogen P. aeruginosa presents the maximum incidence and even becomes predominate among the burn wound pathogens (Gonzalez et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in 2019 across burn patients in India reported the frequency of extensive drug resistance among Pseudomonas isolates as 71.25%. The frequencies of XDR Klebsiella and XDR E. coli were 68.63% and 58.33%, respectively [17]. Although the proportion of XDR pathogens in our study was higher than that reported in India, the general pattern of increased drug resistance among bacteria in burn wounds is comparable.…”
Section: Discussioncontrasting
confidence: 60%
“…In Africa-Middle East countries , K. pneumoniae and E. coli displayed in vitro susceptibility rates of 96.8% and 100%, respectively to tigecycline [ 14 ]. Other studies from India and outside have reported an increasing prevalence of tigecycline resistance in carbapenem-resistant/MDR K. pneumoniae clinical isolates [ [15] , [16] , [17] ]. A study on isolates from burn wound infections in an Indian tertiary care hospital, reported tigecyline resistance in 9.09% and 11.76% of E. coli and K. pneumoniae , respectively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies from India and outside have reported an increasing prevalence of tigecycline resistance in carbapenem-resistant/MDR K. pneumoniae clinical isolates [ [15] , [16] , [17] ]. A study on isolates from burn wound infections in an Indian tertiary care hospital, reported tigecyline resistance in 9.09% and 11.76% of E. coli and K. pneumoniae , respectively [ 16 ]. An increasing prevalence of tigecycline- and carbapenem-resistant K. pneumoniae isolates has been reported from China [ 15 ].…”
Section: Discussionmentioning
confidence: 99%